No Evidence of the “Weekend Effect” in the Northern New South Wales Telestroke Network - Lillicrap, Thomas; Pinheiro, Alex; Miteff, Ferdinand; Garcia-Bermejo, Pablo; Gangadharan, Shyam; Wellings, Thomas; O'Brien, Billy; Evans, James; Alanati, Khaled; Bivard, Andrew; Parsons, Mark; Levi, Christopher; et al. (Frontiers in Neurology, 2020)
Background: Admission outside normal business hours has been associated with prolonged door-to-treatment times and poorer patient outcomes, the so called “weekend effect”. This is the first examination of the weekend effect in a telestroke service that uses multi-modal computed tomography. Aims: To examine differences in workflow and triage between in-hours and out-of-hours calls to a telestroke service. Methods: All patients assessed using the Northern New South Wales (N-NSW) telestroke service from April 2013 to January 2019 were eligible for inclusion (674 in total; 539 with complete data). The primary outcomes measured were differences between in-hours and out-of-hours in door-to-call-to-decision-to-needle times, differences in the proportion of patients confirmed to have strokes or of patients selected for reperfusion therapies or patients with a modified Rankin Score (mRS≤2) at 90 days. Results: There were no significant differences between in-hours and out-of-hours in any of the measured times, nor in the proportions of patients confirmed to have strokes (67.6% and 69.6%, respectively, p=0.93); selected for reperfusion therapies (22.7% and 22.6% respectively, p=0.56) or independent at 3 months (34.8% and 33.6% respectively, p=0.770). There were significant differences in times between individual hospitals, and patient presentation more than 4.5 hours after symptom onset was associated with slower times (21 minute delay in door-to-call, p=0.002 and 22 minute delay in door-to-image, p=0.001). Conclusions: The weekend effect is not evident in the Northern NSW telestroke network experience, though this study did identify some opportunities for improvement in the delivery of acute stroke therapies.